DC 전력공급장치 환경에서 초소형 온라인 직류 무정전 전원공급 장치의 설계 - 이재진 (The Graduate School, Ajou University, 2014)
This paper proposes design method of a mini DC UPS (Uninterruptible Power Supply) for a terminal device using direct connected DC adapters. This paper describes especially the hardware system of mini DC UPS (micro DC UPS). Most of the existing DC UPS systems were developed using a microprocessor to control the input and output voltages. For 12V DC products with FET circuit, the output voltage drops by the circuit characteristics. Therefore, to minimize the effects on output voltage, passive components are used to control the circuit input, output voltages to be stable. In this paper, ripple minimization method is analyzed for when the power is converted from an external source to an internal source. There are summarized in three version results of study, including an actual commercial version. I used relay switches, for connection of external/internal power, without SSR.
학위논문(석사)--아주대학교 일반대학원 :전자공학과,2014. 2